In memoriam of Dr. Abundio Sagástegui Alva (1932 – 2012) - Rodríguez Rodríguez, Eric F. (2012)
On May 26, 2012 after an accident, died in the city of Trujillo, La Libertad, Peru, Professor Dr. Abundio Sagástegui Alva, one of the most distinguished Peruvian scientists. This unexpected disappearance caused deep regret in the Peruvian and international scientific community, because we had left behind a true master, scientist, and botanist, and a human being of great quality.